2023
DOI: 10.3390/ijms24043191
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disrupting Chemicals Influence Hub Genes Associated with Aggressive Prostate Cancer

Abstract: Prostate cancer (PCa) is one of the most frequently diagnosed cancers among men in the world. Its prevention has been limited because of an incomplete understanding of how environmental exposures to chemicals contribute to the molecular pathogenesis of aggressive PCa. Environmental exposures to endocrine-disrupting chemicals (EDCs) may mimic hormones involved in PCa development. This research aims to identify EDCs associated with PCa hub genes and/or transcription factors (TF) of these hub genes in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Our analysis is limited to the human species only. The information about EDCs was obtained from previous literature ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis is limited to the human species only. The information about EDCs was obtained from previous literature ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…RCB is a highly intuitive indicator for assessing the effectiveness of NAC regimens and has also found utility in predicting clinical outcomes in BC patients ( 22 ). Nevertheless, several studies have indicated that even patients achieving pCR after preoperative or postoperative chemotherapy might not experience complete recovery or local control, with some of these tumors still at risk of recurrence ( 23 25 ).…”
Section: Discussmentioning
confidence: 99%